Potential and Concentration Dependent Electrochemical Dealloying of Al2Au in Sodium Chloride Solutions - Xu, Junling; Wang, Yan; Zhang, Zhonghua (Journal of physical chemistry. C, 2012)
Electrochemical dealloying of a single-phase Al2Au alloy in sodium chloride solutions has been investigated considering influence of potential and electrolyte concentration. Both open-circuit potentials and corrosion potentials of Al2Au decrease with increasing electrolyte concentration and temperature. The overpotential and electrolyte concentration have a significant influence on dealloying behaviors of Al2Au, such as steady-state current density and dealloying duration. Nanoporous gold (NPG) can be fabricated by potentiostatic dealloying of Al2Au in the NaCl solutions. Moreover, surface diffusion evaluation demonstrates that there exist good linear relationships between the logarithm of surface diffusivities of Au adatoms (Auad) and overpotential, and between the surface diffusivities of Auad and electrolyte concentration. In addition, the activation energy decreases with increasing overpotential or chloride ion concentration.